2022
DOI: 10.1007/s00394-022-02917-9
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating high-fat diet-induced sperm and testicular oxidative damage by micronutrient-based antioxidant intervention in rats

Abstract: Purpose Emerging evidence from rodent studies suggests that high-fat-diet (HFD)-induced obesity is characterized by increased oxidative damage in sperm and testis. However, interventions using micronutrient supplementation to mitigate oxidative damage in obesity have not been extensively studied. This study aimed to investigate the effect of an antioxidant-based micronutrient supplement (added folate, vitamin B6, choline, betaine, and zinc) on sperm and testicular oxidative damage in HFD-fed male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…A large number of disrupted seminiferous tubule structures, varying degrees of spermatogenetic arrest, and marked morphological damage to the body of sertoli cells are also included in these changes. 26,27 In this study, we found that hyperglycemia increases LPO and, as sperm is very sensitive to peroxidation, 28,29 it seems that hyperglycemia may have a deleterious and destructive effect on the male reproductive system.…”
Section: Discussionmentioning
confidence: 53%
“…A large number of disrupted seminiferous tubule structures, varying degrees of spermatogenetic arrest, and marked morphological damage to the body of sertoli cells are also included in these changes. 26,27 In this study, we found that hyperglycemia increases LPO and, as sperm is very sensitive to peroxidation, 28,29 it seems that hyperglycemia may have a deleterious and destructive effect on the male reproductive system.…”
Section: Discussionmentioning
confidence: 53%
“…This enzyme positively correlates with sperm concentration and overall motility [ 40 ]. Moreover, SOD mRNA transcripts have been found in the testis of rats, with the highest concentration present in tubules just before spermiation [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzyme activity was assessed using the SOD assay [ 23 ]. Retina samples were obtained, homogenized in radioimmunoprecipitation assay buffer at ice-cold temperatures, and centrifuged at 14,000× g for five minutes at 4 °C.…”
Section: Methodsmentioning
confidence: 99%